Strategi Manajemen Data dan Knowledge Management dalam Meningkatkan Efektivitas Organisasi: Studi Kualitatif Pada Instansi Pemerintah di Kota Padang - Barmitoni Barmitoni; Jhon Veri (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to review the literature and bring up the implementation of data management and knowledge management strategies in supporting data-based decision making Materials and methods. Data collection techniques were conducted through in-depth interviews with key informants, such as structural officials, data management staff, and staff involved in the information management and decision-making process.. Results. The main obstacles include low digital literacy, limited infrastructure, and the absence of formal policies. However, employees show a positive perception of the importance of data and knowledge, but are not supported by an adequate system. This study recommends the development of a cloud-based information system, data literacy training, and formal policies for sharing knowledge and strengthening a knowledge-based culture. Conclusions. These results provide importance for the digitalization strategy of the public sector bureaucracy